Duodenal bile acids in infancy. Issue 11 (November 1975) - Challacombe, D N; Edkins, S; Brown, G A
Abstract : Duodenal bile acids have been estimated in three age groups in infancy from birth to 7 months, and age-related changes have been shown. The lowest concentrations of duodenal bile acids occurred in the youngest infants, and increasing concentrations were found with increasing age. Taurine conjugated bile acids predominated in early infancy, while in older infants bile acids were mainly conjugated with glycine. The probable presence of taurolithocholic acid in the duodenal bil of 2 newborns before the establishment of a gastrointestinal microflora remains to be confirmed, but could result either from transplacental passage of secondary bile acids or from endogenous synthesis by the fetal liver.